Psychological features of the relationship between music and emotional states of personality during wartime - KLYMENKO, Iryna; MAKSYMOVA, Olena (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
Background. Global research underscores the significant potential of music as a tool for emotional and physiological regulation, reducing stress reactions, and enhancing overall psychological well-being. In the context of a prolonged war, music can serve as readily accessible resource for maintaining emotional stability among the population of Ukraine and displaced individuals abroad. Investigating the relationship between music and psychological well-being, along with stress coping strategies, while also considering the impact of various musical styles and individual personality traits, is both relevant and practically significant.Methods. Online surveys were conducted with respondents utilizing questionnaires and a comprehensive set of psychological methods to explore five personality factors (BFI-10), psychological well-being (PGWBI), dominant coping strategies (CSI-SF), music preferences (STOMP), and the use of music for mood regulation (B-MMR). Data analysis employed descriptive statistics, Spearman's correlation analysis, confirmatory factor analysis (CFA), exploratory factor analysis, Cronbach's alpha, and Shapiro-Wilk's coefficients.Results. For 81 % of respondents, music holds an important role in their lives. High involvement in musical activities correlates with proactive coping strategies, such as seeking social support and expressing emotions, as well as decreasing distancing behaviors. The predominant personality trait associated with the role of music is agreeableness. Respondents favor reflective and intricate music genres, including classical, jazz, and blues, which they use to experience profound emotions, seek comfort and introspection. The second most notable category includes optimistic and traditional music, such as country, religious or choral music, and pop. Intense and rebellious music styles (alternative, rock, heavy metal) are primarily employed by respondents for emotional release. Emotional regulation strategies like entertainment and distraction show no significant correlation with any particular music style. A slight correlation between music and psychological well-being is observed solely among those for whom music plays a significant role.Conclusions. The study illustrates the connections between the role of music and emotional states, personality traits, music-based regulation methods, psychological well-being, coping strategies, and musical preferences.
Keywords: music; musical preferences; emotional regulation; coping strategies; psychological well-being